Cellular organelles facilitate dimerization of a newly identified Arf from Chlamydomonas reinhardtii. Issue 6 (10th November 2014) - Ranjan, Peeyush; Kashyap, Rudra Shankar; Goel, Manisha; Veetil, Sindhu Kandoth; Kateriya, Suneel; Cock, M.
<x xml:space="preserve">Abstract</x> GTPases of the Ras superfamily regulate a wide variety of cellular processes including vesicular transport and various secretory pathways of the cell. ADP – ribosylation factor (ARF) belongs to one of the five major families of the Ras superfamily and serves as an important component of vesicle formation and transport machinery of the cells. The binding of GTP to these Arfs and its subsequent hydrolysis, induces conformational changes in these proteins leading to their enzymatic activities. The dimeric form of Arf is associated with membrane pinch‐off during vesicle formation. In this report, we have identified an arf gene from the unicellular green alga Chlamydomonas reinhardtii, CrArf, and showed that the oligomeric state of the protein in C. renhardtii is modulated by the cellular membrane environment of the organism. Protein cross‐linking experiments showed that the purified recombinant CrArf has the ability to form a dimer. Both the 20‐kDa monomeric and 40‐kDa dimeric forms of CrArf were recognized from Chlamydomonas total cell lysate (CrTLC) and purified recombinant CrArf by the CrArf specific antibody. The membranous environment of the cell appeared to facilitate dimerization of the CrArf, as dimeric form was found exclusively associated with the membrane bound organelles. The subcellular localization studies in Chlamydomonas suggested that CrArf mainly localized in the cytosol and was mislocalized in vesicle transport machinery inhibitor treated cells. This research sheds light on the importance of the cellular membrane environment for regulating the oligomeric state of CrArf protein in this organism and associated functional role.